BRAND ANALYSIS OF VELOX CREATIVE COMPANY IN INDONESIA - Karan Mahesh Tiwari; Grace Kezia Anang (Journal of the Community Development in Asia (JCDA), 2019)
The basic of this project is to develop Brand Analysis of Velox creative company in Indonesia. The mediums that we will use are Interviews with the personals of the company, social media presence and personal psychology of the peoples with respect to the company. The technique that we are planning to create is brand strategy, various plans, evaluation, metric and estimation. This research will provide valuable information regarding the Brand Strategy, Brand Architecture, Internal Branding, Competitive analysis, Market analysis, Brand metrics, Brand Value and other Brand management attributes. The research will be mostly dependent on the primary and the secondary data that can help us to practical and highly efficient model that will not only benefit the company but also the people. Velox are using online and offline marketing strategy. On online strategy, they are using social media account such as Facebook, Instagram, Email, and also website. On offline strategy, they are using proposal to the potential clients. A client for any company majorly comes from their online strategy and for that we must update our various social media account daily. When we get more followers, our order for work also come from it. As Velox is facing problems with its Brand Marketing and other projections of their work to the world, this gave us an opportunity to sense there some issues and help them with some of our solutions to solve their serious problems. Keywords : Velox, Indonesia, Brand Strategy, Brand Analysis